2021
DOI: 10.1038/s41467-020-20513-5
|View full text |Cite
|
Sign up to set email alerts
|

The circadian cryptochrome, CRY1, is a pro-tumorigenic factor that rhythmically modulates DNA repair

Abstract: Mechanisms regulating DNA repair processes remain incompletely defined. Here, the circadian factor CRY1, an evolutionally conserved transcriptional coregulator, is identified as a tumor specific regulator of DNA repair. Key findings demonstrate that CRY1 expression is androgen-responsive and associates with poor outcome in prostate cancer. Functional studies and first-in-field mapping of the CRY1 cistrome and transcriptome reveal that CRY1 regulates DNA repair and the G2/M transition. DNA damage stabilizes CRY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 83 publications
(141 reference statements)
1
59
0
Order By: Relevance
“…Several attempts have been made to correlate clock gene polymorphisms or expression levels in either cancer cell lines or tissues from various cancers to determine whether clock gene mutations ( 62 ) or levels of expression ( 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ) play a role in initiation or progression of cancer and susceptibility of cancer to a particular drug and a particular time of day for delivery of the drug (chronochemotherapy). The effects of clock gene polymorphism are small, and both predisposing and protective mutations were observed in comparable levels, and thus it is unclear whether these associations have a pathogenic role in the observed phenotypes ( 33 ).…”
Section: Circadian Clock–carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been made to correlate clock gene polymorphisms or expression levels in either cancer cell lines or tissues from various cancers to determine whether clock gene mutations ( 62 ) or levels of expression ( 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ) play a role in initiation or progression of cancer and susceptibility of cancer to a particular drug and a particular time of day for delivery of the drug (chronochemotherapy). The effects of clock gene polymorphism are small, and both predisposing and protective mutations were observed in comparable levels, and thus it is unclear whether these associations have a pathogenic role in the observed phenotypes ( 33 ).…”
Section: Circadian Clock–carcinogenesismentioning
confidence: 99%
“…Similarly, the clock gene expression data lack a time dimension of sampling ( 71 ) and a mechanistic link between the observed clock gene expression changes and the tumorigenic pathways and the suggestion that the -omics findings have been supported by clinical chronochemotherapy trials ( 72 , 73 ) is not in accord with the actual clinical trials. However, the clock gene expression profiles of a select number of cancers may have prognostic value ( 64 , 65 , 68 ).…”
Section: Circadian Clock–carcinogenesismentioning
confidence: 99%
“…Zhao et al, 2013;Puram et al, 2016;W. H. Chang and Lai, 2019;Dong et al, 2019;Shafi et al, 2021). In addition, enhancing intratumor circadian rhythms with clock synchronizing agents (e.g dexamethasone, forskolin, heat shock) results in fewer cells in S phase and more in the G1 phase and inhibits tumor growth .…”
Section: Circadian Regulation Of the Tumor Cell Cycle Can Affectmentioning
confidence: 99%
“…The subsequent rhythm disruptions increase susceptibility to cardiometabolic, digestive, immune, neuropsychiatric disorders, as well as cancers, reflecting the adaptive benefits of circadian rhythms (Masri and Sassone-Corsi, 2018;Scheiermann et al, 2018;Chellappa et al, 2019;Logan and McClung, 2019;Segers and Depoortere, 2021). Studies with animal models containing genetic mutations of clock genes, or animals exposed to circadian desynchrony regimens, reinforce the causal relationship between circadian disturbances and pathology (Mattis and Sehgal, 2016;Aiello et al, 2020;Hadadi et al, 2020;Shafi et al, 2021). In addition to the pathological impact of circadian disruption, symptoms of several medical conditions, including neurological (e.g.…”
mentioning
confidence: 99%
“…Furthermore, a recent study showed that BMAL1 overexpression promotes breast cancer cell invasion and metastasis by upregulating the expression of matrix metalloproteinase 9 (MMP9), a mediating factor for local invasion and distant metastasis of tumors 47 . More recently, CRY1 has been suggested to be a critical factor for efficient DNA repair in tumors, acting as a protumorigenic factor 48 . This is reminiscent of previous studies showing that knockout of Cry1/2 −/− in mice enhances apoptosis pathways in genotoxic responses to UV or cisplatin, a DNA damaging agent, by causing increased expression of the proapoptotic Factor p73 49 .…”
Section: Introductionmentioning
confidence: 99%